Comparison of long‐term and short‐term administration of itraconazole for primary antifungal prophylaxis in recipients of allogeneic hematopoietic stem cell transplantation: a multicenter, randomized, open‐label trial. Issue 2 (5th March 2014) - Lin, R.; Xu, X.; Li, Y.; Sun, J.; Fan, Z.; Jiang, Q.; Huang, F.; Zhou, H.; Nie, D.; Guo, Z.; Mao, Y.; Xiao, Y.; et al.
Abstract Background The optimal agents and duration of primary antifungal prophylaxis in recipients of allogeneic hematopoietic stem cell transplantation (allo‐HSCT) remain a matter of discussion. Objective Our objective was to compare the efficacy and safety of long‐term and short‐term administration of itraconazole (ITCZ) for primary antifungal prophylaxis in allo‐HSCT recipients. Methods This multicenter, randomized, open‐label pilot study was performed in 4 transplant centers in China. Recipients of allo‐HSCT without a history of invasive fungal disease (IFD) were randomly assigned to the long‐term or the short‐term arm. Randomization was carried out by a center computer system. Intravenous ITCZ was given to the patients in both study arms with a loading dose of 400 mg/day for 2 days followed by 200 mg/day until day +14 or when the white blood cell count was >1.0 × 109/L, and then switched to oral ITCZ solution; prophylaxis was continued until day +30 post transplantation in the short‐term arm or until day +90 in the long‐term arm. The trough serum concentrations of ITCZ also were measured. The primary study endpoint was the incidence of IFD (proven, probable, and possible) within day +90 post transplantation. Results A total of 128 recipients were enrolled in this study; 59 of them were randomized to the long‐term arm and 62 were randomized to the short‐term arm, forming the modified intent‐to‐treat (mITT) set. The incidence of IFD within day +90, the primary endpoint, was not significantly different between the 2 arms for the mITT set (6.78% in the long‐term arm vs. 6.45% in the short‐term arm, P = 0.94), or for the per‐protocol set (6.90% in the long‐term arm vs. 6.67% in the short‐term arm, P = 0.96). From day +30 to day +90, the incidence of IFD was 0% and 6.45%, respectively, in the patients with long‐term and short‐term prophylaxis for the mITT set (P = 0.11). The mean trough serum concentrations of ITCZ was maintained at >500 ng/mL throughout administration. The incidences of withdrawal because of drug‐related adverse events in patients with long‐term and short‐term prophylaxis were 6.78% and 0%, respectively (P = 0.05). Conclusions Long‐term and short‐term administration of ITCZ both seemed effective in preventing IFD in recipients of allo‐HSCT. Further study with large sample size should be performed to evaluate this result. ITCZ shows the same pharmacokinetics in recipients of allo‐HSCT as in non‐recipients.